2017
DOI: 10.1016/j.brs.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of motor cortex excitability predicts antidepressant response to prefrontal cortex repetitive transcranial magnetic stimulation

Abstract: Background Repetitive transcranial magnetic stimulation (RTMS) targeting the left dorsolateral prefrontal cortex (DLPFC) is a treatment option for patients with medication-resistant major depressive disorder (MDD). However, antidepressant response is variable and there are currently no response predictors with sufficient accuracy for clinical use. Objective We report on results of an observational open-label study to determine whether the modulatory effect of 10 Hz motor cortex (MC) rTMS is predictive of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 63 publications
2
41
1
Order By: Relevance
“…A neuroimaging study has shown that memory training can drive non-motor brain activation patterns of patients with mild cognitive impairment toward normalization (Belleville et al, 2011). Changes in motor cortical measures after stimulation of non-motor areas have been reported previously (Pallanti et al, 2012), as has prediction of non-motor effects of prefrontal stimulation by motor cortical measures (Oliveira-Maia et al, 2017). These effects could arise through changes in overlapping subcortical glutamatergic and dopaminergic pathways (Wang et al, 2012), which in turn could be driven via cortico-subcortical projections from stimulated non-motor areas.…”
Section: Correlation Of Physiological Measures With Cognitive Performmentioning
confidence: 90%
“…A neuroimaging study has shown that memory training can drive non-motor brain activation patterns of patients with mild cognitive impairment toward normalization (Belleville et al, 2011). Changes in motor cortical measures after stimulation of non-motor areas have been reported previously (Pallanti et al, 2012), as has prediction of non-motor effects of prefrontal stimulation by motor cortical measures (Oliveira-Maia et al, 2017). These effects could arise through changes in overlapping subcortical glutamatergic and dopaminergic pathways (Wang et al, 2012), which in turn could be driven via cortico-subcortical projections from stimulated non-motor areas.…”
Section: Correlation Of Physiological Measures With Cognitive Performmentioning
confidence: 90%
“…The question of whether properties of motor cortex excitability may relate to rTMS response has also garnered some interest. While baseline motor threshold has not been found to be related to treatment response [7], recent work by Oliviera-Maia and colleagues [19] has suggested a potential relationship between modulation of motor cortex excitability prior to rTMS treatment and outcome with DLPFC stimulation. This finding (n = 51) must be considered preliminary due to the small sample size, as well as and the small number of motor evoked potentials used to assess excitability.…”
Section: Motor Cortex Excitabilitymentioning
confidence: 99%
“…A number of rTMS studies have found support for the notion that rTMS may be less effective for depression in older individuals (e.g., [5,[14][15][16]), while others have not found age to be a significant predictor of rTMS outcomes (e.g., [6,7,17,18]). At least one group has found the relationship between age and rTMS outcome to be curvilinear [19]. Greater cortical atrophy has been linked to diminished response to rTMS [20] and strategies have been described to compensate for distance between scalp and cortex in older depressed patients (e.g., [21]).…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%
“…Motor cortical excitability (MCE) measures were the first neurophysiological biomarkers investigated in MDD, as the motor cortex can be easily probed using single- and paired-pulse TMS, which are associated with GABA and glutamate activity in this structure. 181 , 182 Studies have shown that baseline measures of cortical inhibition and facilitation were associated with antidepressant response to tDCS, rTMS, and ECT, 31 , 183 , 184 although effect sizes were small. In addition, EEG-based neurophysiological parameters are associated with antidepressant response to rTMS.…”
Section: Challenges and Opportunities For Precision Non-implantable Nmentioning
confidence: 99%